Terry - Hilton, James, 1900-1954 (Salt Lake City, UT : Project Gutenberg, 2023)
"Terry" by James Hilton is a novel written in the late 1920s. The story follows the enigmatic character M. Terrington, a reserved research lecturer in bacteriology, as he navigates social interactions and personal relationships in London, particularly with Helen Severn, a charismatic young woman who seeks to draw him out of his shell. The narrative unfolds in a slightly melancholic atmosphere, exploring themes of intimacy, professional ambition, and the struggles between personal desires and societal expectations. The opening of "Terry" introduces us to Terrington, who is depicted as a lonely figure attending a dinner hosted by Geoffrey Severn, a successful barrister. His discomfort in social situations becomes evident as he struggles to engage with the other guests, ultimately finding companionship in the narrator, who becomes intrigued by his complexities. The subsequent chapters hint at a developing bond between Terrington and Helen, as she fosters a warmth and curiosity that challenges his reclusive tendencies. As the story progresses, underlying tensions emerge regarding truth, loyalty, and the implications of their growing relationship, setting the foundation for further exploration of their emotional entanglement amid the backdrop of ambition and love. (This is an automatically generated summary.)
Release date is 2023-04-18
Dagny and Laura Natal Rodrigues (Images generously made available by Hathi Trust Digital Library.)
Keywords: English fiction -- 20th century